2010
DOI: 10.1088/1757-899x/10/1/012229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle breakage on cyclic densification of ballast: A DEM approach

Abstract: Vinod, Jayan S.; and Indraratna, Buddhima, 2010, Effect of particle breakage on cyclic densification of ballast: a DEM approach, 1-7. Abstract AbstractIn this paper, an attempt has been made to investigate the effect of particle breakage on densification behaviour of ballast under cyclic loading using Discrete Element Method (DEM). Numerical simulations using PFC2D have been carried out on an assembly of angular particles with and without incorporation of particle breakage. Two-dimensional projection of angula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…A linear contact model, following previous studies, was used for the numerical simulations (e.g. Thakur et al 2010;Indraratna et al 2010b;McDowel et al 2006). …”
Section: Discrete Element Modellingmentioning
confidence: 99%
“…A linear contact model, following previous studies, was used for the numerical simulations (e.g. Thakur et al 2010;Indraratna et al 2010b;McDowel et al 2006). …”
Section: Discrete Element Modellingmentioning
confidence: 99%
“…The discrete element method (DEM) based on discrete particle mechanics introduced by Cundall and Strack (1979) has progressed rapidly over the years and can now model the more insightful micro-mechanical behaviour of granular materials that cannot be examined experimentally (e.g. Sitharam and Vinod 2005;Lobo-Guerrero and Vallejo 2006;Lu and McDowell 2006;Hossain et al 2007;Sitharam and Vinod 2008;Sitharam and Vinod 2009;Huang et al 2009b;Thakur et al 2010;Indraratna et al 2010a;Wang and Gutierrez 2010;O'Sullivan et al 2008;O'Sullivan and Cui 2009;O'Sullivan 2011), among others. The use of DEM to predict the stress-strain response of fouled ballast has been very limited in literature.…”
Section: Introductionmentioning
confidence: 99%
“…The fouling material is produced mainly from the particle crushing of large-size angular ballast particles. The subgrade soil intrusions or outside contaminations such as coal dust from coal trains also produce fouling materials (Selig and Waters, 1994;Thakur et al, 2010;Huang and Tutumluer, 2011). Selig and Waters (1994) reported that the main source of fouling materials in North American railway tracks is the ballast itself, due to the particle crushing (see Fig.…”
Section: Introductionmentioning
confidence: 99%